Antimicrobial resistance, integron carriage, and gyrA and gyrB mutations in Pseudomonas aeruginosa isolated from dogs with otitis externa and pyoderma in Brazil. Issue 2 (1st February 2016) - Arais, Lavicie R.; Barbosa, André V.; Carvalho, Cristiane A.; Cerqueira, Aloysio M. F.
Abstract : Background: Pseudomonas aeruginosa is associated with otitis and pyoderma in dogs and is frequently resistant to several antimicrobial drugs. Resistance genes can be carried by integrons with quinolone resistance mainly due to mutations in DNA topoisomerases II and IV. Objective: To evaluate the antimicrobial susceptibility, integron carriage, and gyrA and gyrB mutations in P. aeruginosa isolates from canine otitis and pyoderma. Animals: One hundred and four P. aeruginosa strains isolated from dogs with otitis externa ( n = 93) and pyoderma ( n = 11). Methods: Antimicrobial susceptibility against 16 antibacterial agents was evaluated through agar diffusion tests. Integron carriage, class and gyrA and gyrB mutations were analysed by PCR, restriction fragment length polymorphism (RFLP)‐PCR and genetic sequencing assays. Results: Isolates were mostly resistant to enrofloxacin (72.2%) and ticarcillin (59.7%). Lower resistance to ciprofloxacin (7.7%), tobramycin (3.8%) and polymixin B (0.0%) was detected. Ten (9.6%) multidrug‐resistant (MDR) strains were detected. Eight (7.7%) strains carried class 1 integrons and this was associated with MDR (three isolates, P ≤ 0.05). Five of the integron‐carrying strains exhibited aminoglycoside resistance genes. Mutations of gyrA and gyrB were observed in 10 isolates, seven of them resistant to all fluoroquinolones tested. Conclusions and clinical importance: Enrofloxacin and ticarcilin resistance was widespread in P. aeruginosa isolated from dogs in Brazil. Pseudomonas aeruginosa carrying integrons may present a significant challenge for treatment. Abstract : Background – Pseudomonas aeruginosa is associated with otitis and pyoderma in dogs and is frequently resistant to several antimicrobial drugs. Resistance genes can be carried by integrons with quinolone resistance mainly due to mutations in DNA topoisomerases II and IV.Objective – To evaluate the antimicrobial susceptibility, integron carriage, and gyrA and gyrB mutations in P. aeruginosa isolates from canine otitis and pyoderma.Conclusions and clinical importance – Enrofloxacin and ticarcilin resistance was widespread in P. aeruginosa isolated from dogs in Brazil. Pseudomonas aeruginosa carrying integrons may present a significant challenge for treatment.